HUBUNGAN REGULASI EMOSI DENGAN KECEMASAN BERBICARA DI DEPAN KELAS PADA SISWA MTS. NURUSSALAM DELI TUA - Amara Arora; Nurul Azmi Saragih; Khairina Ulfa Syaimi; Ika Sandra Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the relationship between emotional regulation and anxiety in public speaking in front of the class in MTs Nurus Salam Deli Tua students in the 2025 Academic Year. This study is based on the importance of public speaking skills in the context of learning and the role of emotional regulation as one of the psychological factors that influence students' anxiety levels. With this study, students are expected to be able to overcome speaking anxiety with emotional regulation. This study uses a quantitative approach with a correlation method and a product moment correlation research design with the help of the SPSS version 23.00 for Windows program. The population in this study were all 8th grade students of MTs Nurus Salam Deli Tua, totaling 180 students, and a sample of 45 students or around 25% of the population was taken using a random sampling technique. The research instrument consisted of an emotional regulation scale and a speaking anxiety scale that had been tested for validity and reliability. The results of the data analysis showed a significant negative relationship between emotional regulation and speaking anxiety in front of the class This is proven by the significance value (p) of 0.001 which is smaller than 0.005, and the correlation coefficient value (r) of -0.491. This means that the higher the students' ability to regulate their emotions, the lower the level of anxiety they experience when speaking in front of the class. Conversely, low emotional regulation ability will be directly proportional to increased speaking anxiety. Thus, it can be concluded that emotional regulation can reduce the level of anxiety in students if the students are able to regulate and manage their emotions. This finding shows the importance of fostering emotional regulation in the context of education, especially to increase students' self-confidence and communication skills in the classroom.